Affine Magic Cubes of Order 4: Concepts and Applications - Siriyakorn Duangmoon; Praphon Kanokladarom; Suchada Pongprasert; Thitarie Rungratgasame; Natsima Srithaisong (International Journal of Mathematics and Mathematical Sciences)
We convert a classical magic cube of order 4, which is an arrangement of 1,2,…,64, to a cube of order 4 whose entries belong to F26. By using finite-dimensional vector spaces over the field F2, we introduce the notion of affine magic cubes and study their properties. The obtained results can be applied to describe some features of various types of magic cubes of order 4.